CspA Influences Biofilm Formation and Drug Resistance in Pathogenic Fungus Aspergillus fumigatus. (3rd March 2015) - Fan, Zhongqi; Li, Zhe; Xu, Zongge; Li, Hongyan; Li, Lixiang; Ning, Cong; Ma, Lin; Xie, Xiangli; Wang, Guangyi; Yu, Huimei
Abstract : The microbial cell wall plays a crucial role in biofilm formation and drug resistance. cspA encodes a repeat-rich glycophosphatidylinositol-anchored cell wall protein in the pathogenic fungus Aspergillus fumigatus . To determine whether cspA has a significant impact on biofilm development and sensitivity to antifungal drugs in A. fumigatus, a Δ cspA mutant was constructed by targeted gene disruption, and we then reconstituted the mutant to wild type by homologous recombination of a functional cspA gene. Deletion of cspA resulted in a rougher conidial surface, reduced biofilm formation, decreased resistance to antifungal agents, and increased internalization by A549 human lung epithelial cells, suggesting that cspA not only participates in maintaining the integrity of the cell wall, but also affects biofilm establishment, drug response, and invasiveness of A. fumigatus .